Hydrogel-based wet adhesive with enhanced adhesion and stretchability - Kang, Byeong Su; Yu, Jin-Young; Bae, Min; Kim, Sei Bin; Cho, Minsu; Kim, Yong Min; Kang, Seong Min (Macromolecular research, 2025)
In this study, we developed a hydrogel wet adhesives characterized by exceptional elasticity and adhesion. The hydrogel composition comprises acrylamide (AM) and [2-(methacryloyloxy) ethyl] dimethyl-(3-sulfopropyl) ammonium hydroxide (SBMA) as monomers. Water and glycerol serve as the solvent, N, N′-methylenebisacrylamide as the crosslinker, and 2-hydroxy-2-methylpropiophenone as the photoinitiator. Notably, SBMA, functioning as a zwitterionic ion, establishes SBMA–SBMA ionic bonds within the hydrogel without crosslinking, thereby enhancing the elasticity of the hydrogel. Furthermore, SBMA promotes adhesion between the hydrogel and other substrates through dipole–dipole interaction forces. Importantly, the resultant high adhesion force remains unaffected by humidity, ensuring maintenance even under high humidity conditions (relative humidity (RH) 90%). By adjusting the AM and SBMA ratio, diverse adhesion forces can be achieved. And, by optimizing the ratio, high stretchability can also be attained. Furthermore, by measuring the adhesion to various substrates, it demonstrates the potential applications of the adhesive by exhibiting stable reactivity. Graphic Abstract Tunable adhesive and enhanced elastic hydrogel-based wet adhesive are proposed by adjusting the acrylamide (AM) and [2-(methacryloyloxy) ethyl] dimethyl-(3-sulfopropyl) ammonium hydroxide (SBMA) zwitterion incorporation.